Student-Initiated Adult-Role Experience: Its Impact on Classroom Climate and Personal Growth - Lee, Dong Yul; Challen, Peter (Canadian Journal of Counselling and Psychotherapy, 2012)
The effects of adolescents' active learning of adult-roles on classroom climate and self-esteem were examined. Tliree classes in a secondary school were randomly assigned to experimental, attention-control, and no-treatment control conditions. The experimental class actively participated in the adult-role experience of teaching third-grade children at a nearby elementary school. The attention-control class held conversation sessions for the same length of time as the experimental class. Results indicated a more positive perception of the classroom environment and an increased sense of self-esteem among the experimental class. The results are discussed in rela- tion to the importance of active rather than passive participation in adult-role experiences.